Novel Spaces as Catalysts for Change: Transformative Learning through Transnational Projects - Helen Caldwell; Emma Whewell; Amy West; Helen Tiplady (MDPI AG, 2024)
This paper discusses data related to the final phase of a six-year project entitled Digital Learning Across Boundaries (DLAB): Developing Changemakers. It explores university students' growing perceptions of themselves as changemakers as they experience novel physical and digital spaces, drawing upon on the reflections of seven undergraduate education students from England who joined students from five European countries in the final year of the project. Using a critical ethnography methodology, this paper embraces reflexivity and immersion in the participants' experiences. Verbal and written reflections were collated and analysed through inductive coding. The results suggest that the multidimensional and multidisciplinary elements of the project led to transformative learning. Transformative change was experienced as students encountered a series of novel spaces and resolved disorientations that arose within them through collective interaction and personal reflection. This paper concludes that educators value the intersection of learning experiences when planning transnational projects and consider the role of cumulative disorientations, multifaceted novel spaces, and critical discourse in catalysing personal growth.